Design, synthesis and bioactivity evaluation of novel thioether derivatives containing a sulfonohydrazide moiety. (1st December 2020) - Li, Pei; Zhou, Junliang; Liu, Yan; Wang, Xiang
Abstract: A series of novel thioether derivatives containing a sulfonohydrazide moiety were synthesized and determined using 1 H NMR, 13 C NMR, HRMS, and elemental analysis. Their in vitro antibacterial activities against Xanthomonas oryzae pv. oryzae ( Xoo ) and Xanthomonas axonopodis pv. citri ( Xac ) were investigated by performing turbidimeter test. Bioassay results showed that some of the target compounds revealed moderate to good antibacterial activities against Xoo and Xac . Especially, N '-(2-(ethylthio)acetyl)-4-fluorobenzenesulfonohydrazide (4p ) revealed the best bioactivities against Xoo and Xac, with the 50% effective concentration (EC50 ) values of 13.75 and 18.56 μg/mL, respectively, which were even better than those of thiodiazole copper and bismerthiazol. Graphical Abstract: UF0001